Physiological Aspects dalam Bahasa Arab; Kajian Psikolinguistik - Cutri A. Tjalau; Saida Gani (Universitas Muhammadiyah Gorontalo, 2022)
Articulatory phonetics is a linguistic study that focuses on the aspects of sound produced through human speech organs. Without the human speech organ, language sounds cannot be produced. Physiological Aspects/Physiological aspects known as articulatory and auditory phonetics explain how the organs of the human body function or play a role in producing language sounds and how sounds are received by the auditory sensory apparatus. The study method used in this research is descriptive qualitative with library research as the type of research. The results of a review of the data obtained found that the physiological aspects of the Arabic language are; 1) Sound Systems/Devices/ الجهاز الصوتي/al-Jiha>z al-Sautiy which are divided into; Lungs / الرئتان /al-Riata>n, Air Pipe/ القصبة الهوائية /al-Qusbah al-Hawa>iyyah, Throat/ Throat Cavity/ الحنجرة أو تجويف الحنجرة/al-Hanjarah aw Tajwi>f al- Hanjarah, Cavity Resonance/ التجاويف الرنينية/al-Taja>wi>f al-Rani>ni>yyah, Tongue/ اللسان /al-Lisa>n, Palate/ الحنك /al-Hank, Teeth and Lips. 2) Organ of Hearing/ الجهاز السمعي/ al-Jiha>z al-Sam'iy",